Antifungal efficacy of microencapsulated oligoDNAs through whey protein concentrate (WPC) as coated protein against Verticillium dahliae - Mahboobeh Nouri; Mojtaba Keykhasaber; Mahdi Pirnia; Mohammad Amin Miri; Shirahmad Sarani; Hoseyn Kamaladini (PLoS ONE, 2026)
Verticillium dahliae is a devastating soil-borne fungal pathogen causing wilting in over 400 plant species, leading to significant economic losses. While nucleic acid-based biocontrol strategies like dsRNA-induced consistent with gene-silencing activity show promise, their application is hindered by poor environmental stability and high production costs. Double-stranded oligodeoxynucleotides (oligoDNAs) offer a stable and cost-effective alternative, but require efficient delivery systems. This study aimed to develop and evaluate the efficacy of novel antifungal microcapsules, encapsulating oligoDNAs (targeting the Clp-1 and HiC-15 genes of V. dahliae ) within a whey protein concentrate (WPC) matrix via electrospraying, for controlling Verticillium wilt. The physicochemical properties of the microcapsules were characterized using SEM, TEM, DLS, FTIR, XRD, TGA, DSC, and BET. Antifungal activity was assessed through in vitro colony growth assays and fluorescence microscopy to visualize oligoDNA uptake. In planta efficacy was evaluated on tomato seedlings by calculating the Disease Index (DI) and Area Under the Disease Progress Curve (AUDPC) over 30 days. Characterization confirmed the successful formation of spherical, oligoDNA-loaded WPC microcapsules with enhanced thermal stability. In vitro , the encapsulated oligoDNA (oligoDNA159 + 166) significantly inhibited fungal colony growth compared to controls, while WPC alone showed no effect. Fluorescence microscopy revealed that Cy3-labeled oligoDNA associated with fungal hyphae, producing discrete punctate signals consistent with cellular uptake, though definitive confirmation of intracellular localization requires higher-resolution imaging techniques. In the greenhouse trial, the encapsulated oligoDNA treatment exhibited the strongest suppression, with a mean DI of 50 (± 10.0) on day 30, corresponding to a 47% reduction compared to the pathogen control. This study demonstrates that WPC-encapsulated oligoDNA is an effective, sustainable, and specific biocontrol agent against V. dahliae . The dual mode of action—direct inhibition of fungal growth and potential host-induced resistance—positions this technology as a promising, environmentally friendly strategy for managing vascular wilt diseases.